"Novel p.Tyr284Cys BEST1 genotype–phenotype correlations of Vitelliform Macular Dystrophy in a family with incomplete penetrance". (3rd March 2020) - Garza-Garza, Lucas Antonio; León-Cachón, Rafael Baltazar Reyes; Aguirre-Garza, Marcelino; Garza-Leon, Manuel
ABSTRACT: Purpose : Vitelliform Macular Dystrophy is an inherited autosomal dominant disease with variable expressivity, caused by a mutation in the BEST1 gene. We report a family with variable expressivity and incomplete penetrance in its members. Materials and Methods : A Mexican family was studied. It was comprised of six individuals (father, mother, and four children). A clinical history was taken, and a complete ophthalmological examination (distance best-corrected visual acuity, slit-lamp biomicroscopy, optical coherence tomography, fundus autofluorescence, optical coherence tomography angiography, and electrophysiological studies) was performed in each individual. Results : Two members presented low visual acuity and vitelliform lesions in different stages in the ocular fundus. The assessment suggested a diagnosis of Vitelliform Macular Dystrophy. Genetic analysis was performed by sequencing of exons 2, 4, 5, 7, 8, and 9 of the BEST1 gene. All patients were carriers of the A variant allele of SNP rs1109748 located in exon 2 (c.219 C > A; p.Ile73=). Also, a missense mutation was identified in exon 7 in the mother and two children (c.851A>G; p.Tyr284Cys). The mother has a normal visual acuity, no abnormal findings in the ophthalmological examination and an abnormal electrooculogram, exhibiting incomplete penetrance. Conclusion : This represents one of the few cases of Vitelliform Macular Dystrophy with incomplete penetrance, being the first in our country and Latin America, and with our reported mutation with this characteristic.